Pengaruh Beberapa Jenis Sirih Terhadap Mortalitas Kutu Beras (Sitophilus oryzae L) - Matondang, Putri Chairani Matondang; Rosa, Helda Orbani; Liestiany, Elly (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
The aim of this research was to determine the effectiveness of administering betel leaf powder from several types of betel on S. oryzae mortality and determine the best type of betel leaf to use to control S. oryzae. This research method is a single factor Randomized Block Design (RAK) consisting of 6 treatments and 4 replications, so there are 24 experimental units. The treatments tested were K0= control (100 g rice + 10 S.oryzae imago) without the addition of betel leaf powder; S1= Green betel leaf powder; S2= Red betel leaf powder; S3= Black betel leaf powder; S4= Forest betel leaf powder; S5 = Yellow betel leaf powder, each treatment of betel leaf powder consists of (6 g betel leaf powder + 100 g rice + 10 S.oryzae imago). The parameters observed were mortality, percentage of rice damage and efficacy. The results of the study showed that the administration of green, red, black, forest and yellow betel leaf powder had an effect on S.oryzae mortality, the percentage of rice damage and showed high effectiveness (efficacy) values ​​for the use of these insecticides. The lowest percentage of rice damage with black betel leaf powder was 11.04% and the highest S. oryzae mortality was recorded with black betel leaf powder treatment with a value of 92.50% and an efficacy value of 80.50%.